2015
DOI: 10.1016/j.ejca.2015.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early tumour shrinkage and resection on outcomes in patients with wild-type RAS metastatic colorectal cancer

Abstract: More patients receiving panitumumab+FOLFOX4 versus FOLFOX4 had ⩾30% or ⩾20% TS at week 8; PFS and OS were also improved with panitumumab+FOLFOX4. The clinical value of achieving early TS in mCRC warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
77
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 23 publications
14
77
1
2
Order By: Relevance
“…ETS, defined as P20% tumour shrinkage at 8 weeks, was observed in 80% of the 57 patients enrolled in the trial. PFS for patients with ETS was significantly prolonged compared with patients without ETS (median PFS 11.5 versus 3.7 months, HR 0.25; 95% CI 0.12- [12,37,38] evaluated tumour response at week 8 in 584 randomised patients with KRASwt tumours according to RECIST (version 1.0) criteria with 30% as the cut-off and ETS defined as P20% at week 8 [38]. Again, the rate of ETS was greater in the panitumumab arm (69% versus 56%), where patients with ETS had a significantly longer PFS (11.0 versus 5.7 months) and OS (30.0 versus 10.7 months) compared to those with no ETS.…”
Section: Ets In Patients Receiving Chemotherapy Plus Egfrtargeting Mabsmentioning
confidence: 99%
“…ETS, defined as P20% tumour shrinkage at 8 weeks, was observed in 80% of the 57 patients enrolled in the trial. PFS for patients with ETS was significantly prolonged compared with patients without ETS (median PFS 11.5 versus 3.7 months, HR 0.25; 95% CI 0.12- [12,37,38] evaluated tumour response at week 8 in 584 randomised patients with KRASwt tumours according to RECIST (version 1.0) criteria with 30% as the cut-off and ETS defined as P20% at week 8 [38]. Again, the rate of ETS was greater in the panitumumab arm (69% versus 56%), where patients with ETS had a significantly longer PFS (11.0 versus 5.7 months) and OS (30.0 versus 10.7 months) compared to those with no ETS.…”
Section: Ets In Patients Receiving Chemotherapy Plus Egfrtargeting Mabsmentioning
confidence: 99%
“…et al [11] and Douillard J.Y. [12] demonstrated that macroscopic liver resection was significantly associated with early tumor response on intravenous chemotherapy. In the present analysis, we determined both early and late responses according to RECIST criteria, qualifying early response as a PR or CR after three treatment courses.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, no significant association was found here between overall best objective response and complete macroscopic liver resection. Recent retrospective studies [12,13,24,25] have addressed this issue through considering early tumor shrinkage as a better indicator of more stringent efficacy outcomes. They defined early tumor response as a relative change of ≥ 20% in the sum of the largest diameters of target lesions at nearly 8 weeks compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving ETS leads to higher rate of treatment response, increased rates of resectability for initially unresectable CLMs, increased overall survival and longer progression-free survival rates in patients with KRAS WT CLMs (regardless the resectability) (118). Most studies showed that ETS is statistically significant more frequent when a combination of CHT with anti-EFGR antibodies is used (118)(119)(120).…”
Section: Liver Resection After Down-sizing Chemotherapymentioning
confidence: 99%